Cu2 - XS films as counter-electrodes for dye solar cells with ferrocene-based liquid electrolytes - Congiu, M. [UNESP]; Nunes-Neto, O. [UNESP]; De Marco, M. L.; Dini, D.; Graeff, C. F.O. [UNESP] (Elsevier, 2016)
In this work, the application of hexagonal CuS nanoparticle layers as counter electrodes for dye sensitized solar cells has been studied. A fast, cheap and reliable deposition method was proposed for the one-step preparation of Cu2 - xS layers on F-doped SnO2 within 30 min through an ink-based technique. The electrodes prepared with our method were tested with iodine/iodide electrolyte, Co(II)/(III) bipyridine redox shuttle and Fe(II)/(III) ferrocene-based liquid electrolyte. The Cu2 - xS layers showed high efficiency and stability with the ferrocene/ferrocenium redox couple, showing a fast charge recombination kinetic, low charge transfer resistance (Rct = 0.73 Ω cm2), reasonably high limiting current (11.8 mA cm- 2) and high stability in propylene carbonate.
Keywords: Copper sulphide; Counter-electrodes; Dye solar cells; Ferrocene; Semiconductors; Solar energy